THE STUDENTS’ DIFFICULTIES IN LEARNING READING - Nadia Nurmalasari; Acep Haryudin (PROJECT (Professional Journal of English Education), 2021)
Based on the occurrences in the field that reading has main role as one of the skill in English. The students must fluent in reading skill because it can help them to referring meaning on their read.This research aimed to find out causes of the difficulties that faced by the students in learning reading and look for answering the problem during learning process. The research using descriptive qualitative to get the problem solving of the research. The data collection of the research are test use to analyse the problem of the students during the reading test and questionnaire use to discover the main reason of their difficulties in reading. By the result of the test, the author can get some point which the number of the question that difficult for the students to answer it. The results is found the reason of their confusion while reading in English. Some aspects influence their motivation to learning hard in reading, the lack of the students knowledge in English vocabulary give the effect they are difficult to arrange the word meaningfor their understanding. Thus, the teacher can be aware to quest the appropriate media to increase their motivation in reading English.Keywords: reading, vocabulary, students difficulties.